2017
DOI: 10.1523/eneuro.0303-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Persistent and Resurgent Sodium Currents in Spiral Ganglion Neurons Cultured from the Mouse Cochlea

Abstract: In spiral ganglion neurons (SGNs), the afferent single units of the auditory nerve, high spontaneous and evoked firing rates ensure preservation of the temporal code describing the key features of incoming sound. During postnatal development, the spatiotemporal distribution of ion channel subtypes contributes to the maturation of action potential generation in SGNs, and to their ability to generate spike patterns that follow rapidly changing inputs. Here we describe tetrodotoxin (TTX)-sensitive Na+ currents in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 62 publications
2
30
0
Order By: Relevance
“…In maturing calyces (P11–P14), we found that 100 nM 4,9-ah-TTX reduced current in 4 cells by ∼25%, whereas at younger ages (P5–10), 4,9-ah-TTX produced a reduction in current in only 2/7 cells suggesting Nav1.6 is not prevalent at early postnatal days, but may be upregulated during development. This is similar to a recent report from mouse cochlea, where resurgent Na + currents appeared in cultured spiral ganglion neurons at the end of the first postnatal week, became more prevalent around hearing onset (P12–14) and were sensitive to block by the Nav1.6 channel toxin 4,9-ah-TTX ( Browne et al, 2017 ). Nav1.6-like immunoreactivity has also been described at the heminode of afferent fibers in the cochlea ( Hossain et al, 2005 ; Kim and Rutherford, 2016 ) and 100 nM 4,9-ah-TTX blocked ∼70% of peak I Na in cultured spiral ganglion neurons ( Browne et al, 2017 ), suggesting that Nav1.6-mediated currents play a key role in action potential firing and conveying sound signals to the central auditory system.…”
Section: Discussionsupporting
confidence: 91%
“…In maturing calyces (P11–P14), we found that 100 nM 4,9-ah-TTX reduced current in 4 cells by ∼25%, whereas at younger ages (P5–10), 4,9-ah-TTX produced a reduction in current in only 2/7 cells suggesting Nav1.6 is not prevalent at early postnatal days, but may be upregulated during development. This is similar to a recent report from mouse cochlea, where resurgent Na + currents appeared in cultured spiral ganglion neurons at the end of the first postnatal week, became more prevalent around hearing onset (P12–14) and were sensitive to block by the Nav1.6 channel toxin 4,9-ah-TTX ( Browne et al, 2017 ). Nav1.6-like immunoreactivity has also been described at the heminode of afferent fibers in the cochlea ( Hossain et al, 2005 ; Kim and Rutherford, 2016 ) and 100 nM 4,9-ah-TTX blocked ∼70% of peak I Na in cultured spiral ganglion neurons ( Browne et al, 2017 ), suggesting that Nav1.6-mediated currents play a key role in action potential firing and conveying sound signals to the central auditory system.…”
Section: Discussionsupporting
confidence: 91%
“…The I NaR , in neurons and other excitable cells is an unconventional Na + current which physiologically activates from a brief membrane depolarization followed by repolarization, such as during an action potential 11, 1417 In the well-studied neuronal Nav1.6-type Na + channels, such a macroscopic I NaR is biophysically suggested to occur from an open-channel block/unblock mechanism 18, 19 . Consequently, I NaR is known to mediate depolarizing after-potentials and promote high-frequency spike discharge in neurons 14, 2024 Sodium channels containing the Nav1.6 subunits carry all three types of sodium currents and are widely distributed in the central and peripheral neurons and participate in burst generation 14, 25 . Sodium channelopathy involving alteration in I NaR and I NaP , and its association with irregular firing patterns and ectopic bursting in disease (e.g., 26–29 ), prompted us to investigate distinct roles for these Na + currents in regulating bursting in sensory neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, β4-subunits have been proposed as the open channel blocker that induced I NaR in cerebellar Purkinje cells, granule cells and dorsal root ganglion neurons ( Grieco et al, 2005 ; Bant and Raman, 2010 ; Barbosa et al, 2015 ). However, the expression of β-subunits has not been characterized in the auditory system, except for a recent finding of β4-subunits in the spiral ganglion neurons of the auditory nerve and calyx of Held at MNTB ( Berret et al, 2016 ; Browne et al, 2017 ). Future experiments will test this speculation.…”
Section: Discussionmentioning
confidence: 99%
“…I NaR is a prevalent property conserved in auditory structures of both avians and mammals and plays an important role in high-frequency AP firing of peripheral and brainstem neurons ( Leao K.E. et al, 2006 ; Kim et al, 2010 ; Browne et al, 2017 ; Hong et al, 2017 ). It remains to be determined if NMc neurons have different Na V channel properties compared to mid- to high-frequency neurons and to what extent – if any – I NaR present with tonotopic heterogeneity that contributes to the distinct AP firing pattern of NMc neurons.…”
Section: Introductionmentioning
confidence: 99%